2022
DOI: 10.3389/fimmu.2022.998975
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression and apoptosis activation mediated by p53-Bcl2/Bax signaling pathway -The potential mechanism of goldfish (Carassius auratus Linnaeus) gill disease caused by Myxobolus ampullicapsulatus

Abstract: Myxobolus, a major harmful type of myxospora, is one of the main parasitic pathogens of freshwater fish. Once myxoboliosis occurs, treatment can be extremely difficult. Therefore, clear understandings of the etiology of myxoboliosis and its pathological mechanism are keys for prevention and control. Here, histology, transmission electron microscopy, transcriptome study, tunel assay, and immunohistochemistry were carried out, revealing the morphology, pathological effects as well as host response mechanism of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Stress signals are transmitted to the p53 protein through post-translational modifications, activating p53 as a transcription factor to initiate processes such as cell cycle arrest, cell senescence, or apoptosis [37]. This enrichment aligned with findings in the transcriptome analysis of goldfish (Carassius auratus Linnaeus) gills infected by Myxobolus ampullicapsulatus, where the role of p53 in triggering apoptosis in fish after infection was illustrated [38]. Furthermore, the FoxO pathway was enriched in both the brain and skin tissues under hypoxia stress.…”
Section: Discussionsupporting
confidence: 63%
“…Stress signals are transmitted to the p53 protein through post-translational modifications, activating p53 as a transcription factor to initiate processes such as cell cycle arrest, cell senescence, or apoptosis [37]. This enrichment aligned with findings in the transcriptome analysis of goldfish (Carassius auratus Linnaeus) gills infected by Myxobolus ampullicapsulatus, where the role of p53 in triggering apoptosis in fish after infection was illustrated [38]. Furthermore, the FoxO pathway was enriched in both the brain and skin tissues under hypoxia stress.…”
Section: Discussionsupporting
confidence: 63%
“…In response to DNA and oxidative stress, p53 accumulates into the cytoplasmic matrix, where it interacts with pro-apoptotic proteins, such as Bax and Bak, BH3-only pro-apoptotic protein initiators, and other members Bcl-2 family of proteins. These molecular interactions may directly or indirectly promote MOMP and tumor cell death by apoptosis [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as we discussed earlier, PLAAT4 expression during pathogen is under the concerted control of p53, IRF1 and IFNs, which all display pleiotropic effects on diverse cellular pathways other than mTOR signaling. For example, they have been demonstrated to play an important role in inducing apoptosis and/ or pyroptosis (146)(147)(148)(149)(150)(151)(152). While our study has shown that PLAAT4mediated suppression of HAV does not involve cell death (16), it remains to be determined whether mTOR-independent signaling pathways (e.g.…”
Section: Mechanisms Of Plaat4 During Antipathogen Restrictionmentioning
confidence: 70%